SYNTHESIS OF CARBOXYETHYLALGINIC ACID AND ITS ETHYL ETHER - T. I. Taradeyko; M. V. Sidorova; A. A. Iozep (Разработка и регистрация лекарственных средств, 2019)
Alkaline hydrolysis of amide carboxyethylalginic acid, obtained by alkylation of alginic acid with acrylamide was carried out. The synthesis of carboxyethylalginic acid, which was not described before in the literature, was carried out. Conditions for obtaining polyacid were studied. The reaction of its esterification was investigated. The effect of acid concentration, reaction time and degree of carboxyethylation of the polysaccharide on the degree of esterification and the yield of the target product were shown.